Applying the green Ca2Al3O6F:Eu2+ oxyfluoride phosphorus on white emitting diodes - Van Liem Bui; Dieu An Nguyen Thi (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
Ca2Al3O6F:Eu2+, a new green-emitting and its photoluminescence (PL) characteristics for white-emitting diodes, have been analyzed and generated (w-LEDs). This phosphorus displays a strong absorption range between ultraviolet (UV) and blue region, along with a wide green emission range of 502 nm. The procedure for concentration suppression and Eu2+ luminous longevity has been investigated using Ca2Al3O6F:Eu2+ phosphors. Key characteristics for manufacturing w-LED lamps, such as photoluminesce based on temperature, microstructure, morphology, CIE value and quantum efficiency, were also investigated in Ca2Al3O6F:Eu2+. The findings show that Ca2Al3O6F:Eu2+, is a suitable option for almost UV-excited w-LEDs as a green component.